Media Komunikasi dalam Peran Dakwah - Efendi, Erwan; Faruq, Muhammad; Amalia, Sylvia; Syakira, Nayaka; Aini, Azizah; Khairunnisa, Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Da'wah patterns have changed over time. Written sermons have now become more important and effective than oral sermons. Especially for works that contain preaching messages and social media. The benefit of da'wah using this model is that as Rasulullah SAW once said,